Pyrazolo[1,5-a]pyrimidin-7-ones as promising antimicrobial scaffolds: In vitro and in vivo evaluation. - Amanda A. Doyle; Mark Kelada; Clara Charleton; Robert Devine; John M.D. Walsh; Ronan Bergin; Kevin Kavanagh; John C. Stephens (Results in Chemistry)
This study presents a family of pyrazolo[1,5-a]pyrimidin-7-ones as potential antimicrobial agents. Initial screening against Staphylococcus aureus, Escherichia coli, and Candida albicans identified compound 3 as active against S. aureus (MIC₅₀ 1.8 μM). A structure activity relationship study of 35 analogues yielded the more potent analogues (MIC₅₀ 1.2 μM, MIC₈₀ 6.4 μM). Hit compounds were further evaluated against Methicillin-Resistant S. aureus (MRSA) and Pseudomonas aeruginosa, with pyrimidinone 12 showing the strongest activity against MRSA (MIC₅₀ 1.88 μM, MIC₈₀ 2.93 μM). In vivo toxicity assessment using Galleria mellonella larvae indicated that the leading active compounds were non-toxic. Importantly, in an in vivo G. Melonella MRSA infection model, compound 12 improved survival by 25 % compared to untreated controls (95 % vs. 75 %, p < 0.05). These strong in vivo results highlight pyrazolo[1,5-a]pyrimidin-7-ones as promising scaffolds for the development of new antibacterial agents.